Perencanaan Dan Pengendalian Persediaan Spare Part Mesin Di Unit Produksi 1 PT. Petrokimia Gresik Menggunakan Kebijakan Can-Order - Alfan Zaldiansyah; Wakhid Ahmad Jauhari; Azizah Aisyati (Performa: Media Ilmiah Teknik Industri, 2013)
This research was carried out on one of the fertilizer industry. This industry have numerous itemof machine spare part. The problem concerned with machine spare parts controlling which is theordering of them are done separately, that makes inventory cost and order frequency become quite high. Therefore, inventory control of machine spare part will be done by using a coordinated ordering system with model of can-order policy. Parameters determination (S,c,s) was held on 7 items of machine spare part that was ordered from 1 supplier with using algorithm can order policy. Then, the total cost of inventory was calculated based on parameter of can order and will be compared with existing company system using monte carlo simulation. This comparing result shows the model of can order policy is more efficient to control machine spare part inventory which saving 52 % than the total inventory cost using existing company system.